Pengaruh Brand Image Dan Persepsi Harga Terhadap Keputusan Pembelian: (Survei pada Konsumen Toko QueenzaBella Fashion Ciawi Tasikmalaya) - Risma Shafitri (J-CEKI : Jurnal Cendekia Ilmiah, 2022)
This study aims to determine the simultaneous and partial effect of Brand Image and Price Perception on Purchase Decisions at the Queenzabella Fashion Ciawi Tasikmalaya Store. The method used in this research is descriptive and quantitative methods. The population studied were 100 respondents. The data collected in the form of primary data and secondary data. Data analysis in this study used multiple regression analysis using SPSS 24 software. The results showed that brand image and price perception simultaneously had a significant effect on purchasing decisions at the Queenzabella Fashion Ciawi Tasikmalaya Store. Brand image partially has a significant effect on purchasing decisions at the Queenzabella Fashion Ciawi Tasikmalaya store. Price perception partially has a significant effect on purchasing decisions at the Queenzabella Fashion Ciawi Tasikmalaya Store.